2024
DOI: 10.1021/acssuschemeng.3c04729
|View full text |Cite
|
Sign up to set email alerts
|

Copper Ion-Induced Self-Assembled Aerogels of Carbon Dots as Peroxidase-Mimicking Nanozymes for Colorimetric Biosensing of Organophosphorus Pesticide

Guotao Yi,
Ziwen Tao,
Wenfang Fan
et al.

Abstract: Establishing a rapid and sensitive biosensing method for organophosphorus pesticide (OP) is essential because of its pollution to the environment and potential harm to human health. In the report, copper ion-induced selfassembled aerogels of carbon dots are coupled with acetylcholinesterase and choline oxidase to construct a multienzyme cascade catalysis-based colorimetric biosensor for the detection of OP dichlorvos. The copper−carbon dot aerogels (Cu-CDs) are massively fabricated using copper as the metal bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…It can be seen that Cu 2p, Ag 3d, and Se 3d elemental signals were observed in the XPS spectrum of CSA. In the Cu 2p spectra (Figure H), the peaks at 931.7 and 951.2 eV were assigned to Cu + or Cu 0 , and the peaks at 933.92 and 954.62 eV were assigned to Cu 2+ , ,, implying a mixed valence state of copper elements in the synthesized CSA nanoparticles. For the high-resolution XPS of Se 3d (Figure I), the peaks at 53.8 and 53.3 eV corresponded to Se 3d 3/2 and Se 3d 5/2 , respectively, and the peak at 57.8 eV is due to SeO x . In the Ag 3d spectrum (Figure J), the appearance of the peaks at 368.5 and 374.5 eV was indexed to Ag 3d 5/2 and Ag 3d 3/2 , respectively, demonstrating that the valence state of Ag was zero and the formation of pure metallic Ag on the surface of CS. , These results indicated that the as-prepared CSA possesses desirable characteristics for biomedical applications.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It can be seen that Cu 2p, Ag 3d, and Se 3d elemental signals were observed in the XPS spectrum of CSA. In the Cu 2p spectra (Figure H), the peaks at 931.7 and 951.2 eV were assigned to Cu + or Cu 0 , and the peaks at 933.92 and 954.62 eV were assigned to Cu 2+ , ,, implying a mixed valence state of copper elements in the synthesized CSA nanoparticles. For the high-resolution XPS of Se 3d (Figure I), the peaks at 53.8 and 53.3 eV corresponded to Se 3d 3/2 and Se 3d 5/2 , respectively, and the peak at 57.8 eV is due to SeO x . In the Ag 3d spectrum (Figure J), the appearance of the peaks at 368.5 and 374.5 eV was indexed to Ag 3d 5/2 and Ag 3d 3/2 , respectively, demonstrating that the valence state of Ag was zero and the formation of pure metallic Ag on the surface of CS. , These results indicated that the as-prepared CSA possesses desirable characteristics for biomedical applications.…”
Section: Resultsmentioning
confidence: 97%
“…These results validated that CSA indeed has the potential to generate • OH, O 2 •– , and 1 O 2 and that its catalytic activity could be enhanced by laser irradiation. The possibly catalytic mechanisms can be described as follows ,, normalC normalu + + H 2 O 2 normalO normalH + normalC normalu 2 + + normalO normalH normalO normalH + H 2 O 2 normalO 2 + H 2 normalO + H + H 2 normalO + normalO 2 normalO 2 1 + normalO normalH + H 2 O 2 normalC normalu 2 + + normalO 2 normalO 2 1 + normalC normalu + In the catalytic system of CSA, H 2 O 2 was adsorbed on the CSA surface and activated by Cu(I) in CSA, leading to the generation of • OH, while...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation